The role of COPD in survival of NSCLC patients receiving immune checkpoint inhibitors: A meta-analysis - Yan Zhu; Chongyang Wang (Biomolecules & Biomedicine)
The impact of chronic obstructive pulmonary disease (COPD) on the survival of patients with non-small cell lung cancer (NSCLC) receiving immune checkpoint inhibitors (ICIs) remains unclear. Given the growing use of ICIs in NSCLC treatment and the high prevalence of COPD among these patients, understanding this relationship is essential. This meta-analysis aims to evaluate the association between COPD and survival outcomes in NSCLC patients treated with ICIs. A systematic search was conducted in PubMed, Embase, and Web of Science from inception to February 10, 2025. Observational studies reporting survival outcomes in NSCLC patients with and without COPD undergoing ICI therapy were included. Hazard ratios (HRs) with 95% confidence intervals (CIs) were pooled using a random-effects model to account for heterogeneity. Thirteen retrospective cohort studies involving 5,564 patients were included. COPD was associated with improved progression-free survival (PFS) (HR: 0.68, 95% CI: 0.54–0.85, p < 0.001) and overall survival (OS) (HR: 0.80, 95% CI: 0.68–0.95, p = 0.01) in NSCLC patients receiving ICIs. Heterogeneity was moderate (I² = 46% for PFS, I² = 43% for OS). Subgroup analyses indicated that the association between COPD and survival outcomes was consistent across study regions (Asian vs. Western countries), patient age, sex distribution, COPD diagnostic criteria (spirometry, clinical diagnosis, or CT-diagnosed emphysema), follow-up duration, analytic models (univariate vs. multivariate), and study quality scores (p for subgroup differences > 0.05). Furthermore, univariate meta-regression analysis showed no significant modification of results by sample size, mean age, sex distribution, follow-up duration, or study quality scores (all p > 0.05).